STUDI TAFSIR AN-NUR KARYA HASBI ASH-SHIDDIEQY - Sarimin Adang; Muhith (STKIP Subang, 2026)
The study of Qur’anic exegesis in the Indonesian context plays a significant role in understanding interpretations that are responsive to social realities. One of the prominent works in Indonesian Qur’anic scholarship is Tafsir An-Nur by Hasbi Ash-Shiddieqy, which reflects a modern approach to Qur’anic interpretation. This research aims to examine the characteristics, methods, and interpretative approaches employed in Tafsir An-Nur, as well as its contribution to the development of Nusantara tafsir. This study employs a library research method with a qualitative-descriptive approach. Data were collected through documentation of Tafsir An-Nur as the primary source and relevant supporting literature, and analyzed using content analysis techniques. The findings indicate that Tafsir An-Nur applies a systematic and accessible interpretative method, emphasizing rational and contextual understanding. The work seeks to connect Qur’anic teachings with the social conditions of Indonesian society, making the interpretation practical and comprehensible. This study concludes that Tafsir An-Nur significantly contributes to the development of modern Indonesian Qur’anic exegesis that is moderate, rational, and socially relevant.